Karakteristik Campuran Aspal Porus Dengan Menggunakan Material Dari Lampung - Suryatama, Noval; Putra, Sasana; herianto, dwi; Sulistyorini, Rahayu (Universitas Lampung, 2023)
Porous asphalt is one of the asphalt mixtures being developed for wearing course construction. This layer uses open graded which is dominated by coarse aggregate, resulting in quite large voids. The material used in this study came from Lampung. The purpose of this study was to determine the characteristics of porous asphalt mixtures using materials from Lampung. The results of the aggregate testing show that aggregates originating from Lampung are able to meet the general specifications of Bina Marga in 2018. This study shows that the highest stability is found at 5.5% asphalt content with a stability value of 552.52 kg and the lowest stability at 6.5 asphalt content % with a stability value of 459.22 kg. The lowest flow value is found at 5% asphalt content, which is 5 mm, while the highest flow value is found at 6.5% asphalt content, which is 6.2 mm. The highest VIM was found at 4.5% asphalt content which was 21.77%, while the lowest VIM value was found at 6.5% asphalt content which was 14.07%. The highest cantabro loss value was found at 4.5% asphalt content, which was 39.11%, while the lowest cantabro loss value was found at 6.5% asphalt content, which was 13.91%. The lowest asphalt flow down value is found at 4.5% asphalt content, which is 0.16%, while the highest AFD value is found at 6.5% asphalt content, which is 1.30%. Based on the test specimens for the optimum asphalt content, the permeability coefficient value was 0.075 cm/second.